PENGARUH PRAKTIK TOTAL QUALITY MANAGEMENT TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT ERIA PEKANBARU - Saragih Septian Andre; Restu Restu; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Total Quality Management (TQM) is a way to maximize the performance of an organization that involves human resources and available capital for patient satisfaction. This research is a quantitative research using multiple linear regression test. This study aims to determine the effect of Total Quality Management (TQM) which includes a focus on customers, system improvement, as well as involvement and empowerment on the performance of nurses at Eria Hospital Pekanbaru. The sample in this study were all nurses at Eria Hospital Pekanbaru, totaling 73 respondents from the population. The data collection method used is a questionnaire. Primary data were collected using a questionnaire as an instrument. To test the hypothesis in this study, IE by using multiple linear analysis with the help of SPSS version 23. The results of this study indicate that Total Quality Management which consists of variables focused on customers, improvement of the cooperation system, and employee involvementand empowerment has a positive and significant effect on performance. is 72.1% while the remaining 27.9% is influenced by other variables that are not included in this regression model. Nurses at Eria Hospital Pekanbaru, either simultaneously or partially.Keywords: Total Quality Management (TQM), Nurse Performance